Characteristics of catfish (Clarias sp.) smart flavor with enzymatic hydrolysis using calotropin - Witono, Yuli; Kartikosari, Dini Indah; Azkiyah, Lailatul; Wahyuni, Livia (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
Savory flavor generally comes from Monosodium Glutamate (MSG), but increased consumption of MSG can have side effects on health. Catfish, which contains 17.7% protein, has the potential to impart a savory flavor. This research aimed to determine the effects of calotropin enzyme concentration and hydrolysis time on the development of smart flavor characteristics and identify the best treatment to produce smart flavor. This study used two-factors: calotropin enzyme concentration (1, 2 and 3%) and hydrolysis time (2, 4 and 6 hours). The research parameters included color (brightness), yield, water content, soluble protein content, degree of hydrolysis, antioxidant activity, and effectiveness analysis. The results showed that the color (brightness) ranged from 90.73-91.81; yield from 77.01-78.95%; water from 8.63-10.40%; soluble protein from 0.89-1.30 mg/mL; degree of hydrolysis from 46.61-58.19%; antioxidant activity from 42.18-54.14%, and effectiveness ranged from 0.15-0.85. The best treatment was found to be 3% calotropin enzyme concentration with 6 hours of hydrolysis, resulting in color (brightness) of 90.73, yield of 78.95%, water of 8.63%, soluble protein of 1.30 mg/mL, degree of hydrolysis of 58.19%, and antioxidant activity of 54.14%.